Study of Causes, Methods and Complications of Early and Late Miscarriage due to Intentional Abortion in Women referred to Health Centers covered by Shahid Beheshti University - Abdoljabbari, Morteza; Saharkhiz, Nasrin; Karamkhani, Marzieh; Rahmani, Reza (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: Induced abortion is a major threat to women’s fertility health. In particular, in developing countries and the societies where abortion is illegal, abortions are commonly carried out under unsanitary conditions, causing maternal complications, dangers to maternal health, and women’s future infertility. These consequences are especially evident in Iran where at least 80,000 illegal abortions are done annually. The current study aimed to examine the reasons for abortion, methods of abortion, and its short-term and long-term complications. Methods: This study, which adopted a descriptive design, was conducted among the women who had already carried out abortion and referred to one of the health, therapeutic, and educational centers affiliated with Shahid Beheshti University of Medical Sciences. The participants (N = 360) were selected the data were gleaned through a self-designed questionnaire and statistically analyzed using SPSS version 17. Results: The results of analyzing the data collected through the 369 questionnaires revealed that the mean age of participants was 26 years (SD = 7.2 years). The main reason for abortion was financial problems. With regard to marital status, 91.3% of the participants were married. Also, considering their job, 74.2% of the respondents were housewives, while 15.5% were employed in office jobs. Further, in 55.3% of the cases, abortion had been carried out as a result of the husband’s encouragement. The most common method of abortion was prescribing chemical medications, while the least popular method was intrauterine manipulations (with only 197 women reporting this abortion method). Moreover, 114 participants reported that they had accomplished curettage in a specialist physician’s office without anesthesia. The short-term complications of abortion included abdominal pain after abortion and incomplete abortion. On the other hand, long-term complications entailed visceral injury (1%), complications in the next pregnancy, bleeding in early pregnancy (10.7%), preterm delivery (7.9%), and ectopic pregnancy (7.4%). Conclusions: Scientific and religious education through appropriate procedures along with preventing unwanted pregnancy is a decisive factor in abortion.